THE EFFECT OF THE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) LEARNING MODEL ON THE SCIENCE LEARNING OUTCOMES OF GRADE IV STUDENTS OF UPTD SD NEGERI 122345 PEMATANGSIANTAR IN THE 2025/2026 ACADEMIC YEAR - Lely Afriani Lumban Raja; Imelda Sabrina Sibarani; Jon Roi Tua Purba (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the Effect of Using the Student Teams Achievement Divisions (STAD) Learning Model on the Science Learning Outcomes of Fourth Grade Students of UPTD SD Negeri 122345 Pematangsiantar. This type of research is Quantitative experimental method One Group Pretest-Posttest Design. The population of this study were all fourth grade students of UPTD SD Negeri 122345, totaling 26 students. This research was conducted in August of the 2025/2026 academic year. The test technique that will be given in this study is multiple choice questions on the material of Plant Parts. Data were analyzed using the normality test (Shapiro-Wilk) and the score increase test (N-Gain). The results showed that the average student pretest score was 58.7 with a completion rate of 23%, which then increased to 86.6 with a completion rate reaching 96.2% in the posttest. Based on the results of inferential statistical analysis using the partial test formula or t-test with a frequency (dk) of 26-1 = 25 at a significance level of 5%, 1.708 was obtained and from the results of the student test, t_hitung = 15.61 was obtained. Therefore, t_hitung > t_tabel = 15.61 > 1.708, which means that H_o is rejected and H_a is accepted, which means that there is an influence of the Student Teams Achievement Divisions (STAD) Learning Model on the learning outcomes of Class IV students of UPTD SD Negeri 122345 Pematangsiantar in the 2025/2026 academic year.